Sputtering growth of Y3Fe5O12/Pt bilayers and spin transfer at Y3Fe5O12/Pt interfaces - Houchen Chang; Tao Liu; Danielle Reifsnyder Hickey; P. A. Praveen Janantha; K. Andre Mkhoyan; Mingzhong Wu (APL Materials, 2017)
For the majority of previous work on Y3Fe5O12 (YIG)/normal metal (NM) bi-layered structures, the YIG layers were grown on Gd3Ga5O12 first and were then capped by an NM layer. This work demonstrates the sputtering growth of a Pt/YIG structure where the Pt layer was grown first and the YIG layer was then deposited on the top. The YIG layer shows well-oriented (111) texture, a surface roughness of 0.15 nm, and an effective Gilbert damping constant less than 4.7 × 10−4, and the YIG/Pt interface allows for efficient spin transfers. This demonstration indicates the feasibility of fabricating high-quality NM/YIG/NM tri-layered structures for new physics studies.